Rapid quantification of malondialdehyde in plasma by high performance liquid chromatography–visible detection - Grotto, D.; Santa Maria, L.D.; Boeira, S.; Valentini, J.; Charão, M.F.; Moro, A.M.; Nascimento, P.C.; Pomblum, V.J.; Garcia, S.C. (Journal of pharmaceutical and biomedical analysis, 2007)
Malondialdehyde (MDA) is one of the better-known secondary products of lipid peroxidation, and it is widely used as an indicator of cellular injury. The employment of the thiobarbituric acid reactive substances (TBARS) technique to measure MDA has received criticism over the years because of its lack of specificity. Thus, a specific and reliable method for MDA determination in plasma by high performance liquid chromatographic (HPLC)–VIS was validated; alkaline hydrolysis, n-butanol extraction steps and MDA stability were established. The plasma underwent alkaline hydrolysis, acid deproteinization, derivatization with TBA and n-butanol extraction. After this, MDA was determined at 532 nm by HPLC–VIS. The method was applied to 65-year-old subjects from a retirement home. The assay was linear from 0.28 to 6.6 μM. The reproducibility of intra-run was obtained with CV% < 4% and the inter run with CV% < 11%. The accuracy (bias) ranged from 2 to −4.1%, and the recovery was greater than 95%. The limit of detection (LOD) and limit of quantification (LOQ) were 0.05 and 0.17 μM, respectively. For the stability test, every sample was stored at −20 °C. The plasma MDA was not stable when stored after the alkaline hydrolysis step, remained stable for 30 days after TBA derivatization storage and was stable for 3 days when stored after n-butanol extraction. The elderly subjects had MDA plasma levels of 4.45 ± 0.81 μM for women and 4.60 ± 0.95 μM for men. The method is reproducible, accurate, stable, sensitive, and can be used in the routines in clinical laboratories. Besides, this technique presents advantages such as the complete release of protein bound MDA with the alkaline hydrolysis step, the removal of interferents with n-butanol extraction, mobile phase without phosphate buffer and rapid analytical processes and run times.